2014
DOI: 10.1158/1055-9965.epi-14-0593
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention and Control Interventions Using Social Media: User-Generated Approaches

Abstract: Social media are now used by a majority of American internet users. Social media platforms encourage participants to share information with their online social connections and exchange user-generated content. Significant numbers of people are already using social media to share health-related information. As such, social media provide an opportunity for “user-generated” cancer control and prevention interventions that employ users' behavior, knowledge, and existing social networks for the creation and dissemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 22 publications
(22 reference statements)
0
27
0
Order By: Relevance
“…A growing body of research has shown that AYAs with cancer are comfortable with and interact through multiple modes of in‐person and Web‐based information support . Future research in this area should examine interventions with social media and social networking tools to build peer‐survivor relationships and improve social support for AYAs …”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has shown that AYAs with cancer are comfortable with and interact through multiple modes of in‐person and Web‐based information support . Future research in this area should examine interventions with social media and social networking tools to build peer‐survivor relationships and improve social support for AYAs …”
Section: Discussionmentioning
confidence: 99%
“…One potential reason for our lower login average is that the website was able to automatically pull data from devices such as the FitBit without the participants having to login. One recent suggestion for increasing user engagement is to allow user-generated content (eg, creating a post to add to the newsfeed) [44] which may increase user “buy-in.” This method, however, requires close monitoring as information would need to be vetted to ensure accuracy and relevance. Retaining and engaging participants remain an issue among Internet-delivered behavior change programs.…”
Section: Discussionmentioning
confidence: 99%
“…37 Research consistently has found that posting photos results in a greater amount of engagement than other post types. 31,38,39 A study of scientific communication with the public across social media platforms by the European Organization for Nuclear Research found that “wow” photographs (i.e., awe-inspiring photographs) produced the most engagement, especially when posted on the photo-emphasizing platform Instagram.…”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 98%